تأثير كفاءة سوق المستثمر في تحديد التوازن الظرفي لخصائص المعلومات المحاسبية - أ.د. قاسم محسن الحبيطي; شكر محمود مصطفى (PROSPECTIVE RESEARCHES, 2023)
The main objective of Accounting, is represented in providing useful information that guides investment decisions, as the accounting information is regarded as the basic pillar on which investment decision is based . In order that the accounting information could produce this effect, it is necessary to be of specific level of quality that it is vested in individual characteristic for such information. One of most important of these characteristics are " suitability and creditability", when the concern of the investor either concentrates on the timing in obtaining the information or on the degree of creditability required. The research problem arise out of different references of accounting information user of the investors in various quality characteristics which should be available in such information, and this deference will generate different balancing points for these characteristics. The research depends on two propositions l. The balance of quality characteristics in the accounting information is regarded as one of the component's efficient proposition of the financial security market. 2. Balancing circumstantial characteristic accounting information in more than on point on " preferential curve " in the efficient financial market. The researchers used in deferent curves analysis as on of the modern techniques, used in the micro economic theory end edgwardth box, to determine a combination of accounting information quality characteristic through indifference curve for the accountant as the provider of accounting information which is required by each of: - The shrewd investor (careful). - The aggressive investor (income investor). - The risk avoidance investor (capital investor).